Healthcare workers' behaviors on infection prevention and control and their determinants during the COVID-19 pandemic: a cross-sectional study based on the theoretical domains framework in Wuhan, China - Qiuxia Yang; Xuemei Wang; Qian Zhou; Li Tan; Xinping Zhang; Xiaoquan Lai (BMC, 2021)
Abstract Background Infection prevention and control (IPC) measures are crucial to combat the COVID-19 pandemic. This study aimed to explore the levels and determinants of HCWs' IPC behaviors based on the theoretical domains framework (TDF), which has been shown to be effective in guiding behavior change. Methods A cross-sectional survey was conducted in Wuhan, China in January 2020. Self-reported hand hygiene and droplet isolation behaviors (including the use of masks, gloves, goggles and gowns) were set as dependent variables. TDF domains and HCWs' characteristics were independent variables. Negative binomial regression analyses were performed to explore their relationships. Results HCWs reported good IPC behaviors, while the compliance with goggle and gown use was relatively low (below 85%). Environmental context and resources domain was significantly related to hand hygiene (β = 0.018, p = 0.026), overall droplet isolation behaviors (β = 0.056, p = 0.001), goggle (β = 0.098, p = 0.001) and gown use (β = 0.101. p < 0.001). Knowledge domain was significantly related to goggle (β = 0.081, p = 0.005) and gown use (β = 0.053, p = 0.013). Emotion domain was a predictor of overall droplet isolation behaviors (β = 0.043, p = 0.016), goggle (β = 0.074, p = 0.026) and gown use (β = 0.106, p < 0.001). Social influences domain was a predictor of overall droplet isolation behaviors (β = 0.031, p = 0.029) and gown use (β = 0.039, p = 0.035). HCWs in high-risk departments had better behaviors of gown use (β = 0.158, p = 0.032). HCWs who had encountered confirmed or suspected patients reported worse behaviors of goggle (β = − 0.127, p = 0.050) and gown use (β = − 0.153, p = 0.003). Conclusions Adequate personal protective materials and human resources, education and training, as well as supervision and role model setting are necessary to improve IPC behaviors regarding the COVID-19 pandemic.